Clinical translation of anti-inflammatory effects of Prevotella histicola in Th1, Th2, and Th17 inflammation - Itano, Andrea; Maslin, Douglas; Ramani, Kritika; Mehraei, Golbarg; Carpenter, Nancy; Cormack, Taylor; Saghari, Mahdi; Moerland, Matthijs; Troy, Erin; Caffry, Will; Wardwell-Scott, Leslie; Abel, Stuart; et al. (Frontiers in Medicine, 2023)
We report here preclinical and clinical studies showing that the action of EDP1815, an orally delivered and gut restricted single strain of commensal bacteria can regulate inflammatory responses throughout the body. The gut is the largest immune organ in the body and its surface area provides the body’s largest contact with the environment. Immune cells in the epithelial lining of the small intestine encounter the environmental content that passes through the lumen and transmits signals around the body via lymphatic, vascular and neurological connections altering systemic physiology. This is the first report demonstrating clinical effects from targeting this axis with a non-colonizing single strain of commensal bacteria, providing proof of concept for a new class of medicines. EDP1815 is a non-colonizing pharmaceutical preparation of a single stain of Prevotella histicola isolated from the duodenum of a human donor. It has previously been reported to reduce inflammation after oral administration in both EAE and CIA mouse models of neurological and joint inflammation. We have now extended these observations to a range of preclinical Th1, Th2 and Th17 mouse models showing the breadth and potency of pre-clinical activity. We then demonstrate translation of these effects to humans in a T cell-driven skin challenge model in healthy human volunteers, the predominantly Th2-driven disease atopic dermatitis, and the predominantly Th17-drive disease psoriasis. These clinical effects occur without systemic exposure of EDP1815 or modification of the resident gut microbiota, and with placebo-like safety and tolerability. The breadth of these clinical effects of EDP1815, combined with its excellent safety and tolerability profile and oral administration, suggests the potential for a new type of effective, safe, oral, and accessible anti-inflammatory medicine to treat the wide range of diseases driven by inflammation. [Clinical study identifiers: EudraCT # 2018-002807-32; EudraCT # 2018-002807-32; NL8676; https://clinicaltrials.gov/ct2/show/NCT03733353; http://www.trialregister.nl]